2011
DOI: 10.1002/iub.423
|View full text |Cite
|
Sign up to set email alerts
|

A novel single‐chain variable fragment antibody against FGF‐1 inhibits the growth of breast carcinoma cells by blocking the intracrine pathway of FGF‐1

Abstract: SummaryThe fibroblast growth factors (FGFs) are important for embryo development, wound healing, hematopoiesis, and angiogenesis. FGF-1, a member of FGF family, is involved in both receptor-dependent pathways and an intracrine pathway. Studies have recently shown that FGF-1 is overexpressed in the early stages of several kinds of cancer. Thus, FGF-1 is a candidate for cancer immunotargeting. To study the potential use of therapeutic antibodies against FGF-1, a monoclonal hybridoma 1C9 secreting monoclonal anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Mouse immunoglobulin VH and VL genes were amplied for each mAb using the primers in the RPAS Mouse scFv Module (GE Healthcare Bio-Sciences, Shanghai, China). 16 The following thermal conditions were used for polymerase chain reaction (PCR) analysis of the VH genes: 30 cycles of 94 C for 30 s, 65 C for 30 s, and 72 C for 40 s, followed by a nal extension at 72 C for 7 min; the following thermal conditions were used for PCR analysis of the VL genes: 25 cycles of 94 C for 30 s, 65 C for 1 min, and 72 C for 1 min, followed by a nal extension at 72 C for 7 min.…”
Section: Cloning Of the Mab Variable Region Genesmentioning
confidence: 99%
“…Mouse immunoglobulin VH and VL genes were amplied for each mAb using the primers in the RPAS Mouse scFv Module (GE Healthcare Bio-Sciences, Shanghai, China). 16 The following thermal conditions were used for polymerase chain reaction (PCR) analysis of the VH genes: 30 cycles of 94 C for 30 s, 65 C for 30 s, and 72 C for 40 s, followed by a nal extension at 72 C for 7 min; the following thermal conditions were used for PCR analysis of the VL genes: 25 cycles of 94 C for 30 s, 65 C for 1 min, and 72 C for 1 min, followed by a nal extension at 72 C for 7 min.…”
Section: Cloning Of the Mab Variable Region Genesmentioning
confidence: 99%
“…More recently, several studies indicate that specific FGFs and FGF receptors (FGFRs), such as FGF2, FGF9, FGFR1, FGFR2, and FGFR3, are overexpressed or mutated in NSCLC cells and associated with poor prognosis of patients [6][7][8][9]. Similar with FGF2 and FGF9, FGF1 also is identified as a candidate cancer biomarker [10]. However, as far as we know, there is no study focused on the expression and function of FGF1 in NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Revealing the working mechanism of hscFv1C9 is needed to promote its medical possibility. We had previously shown that the intracellular expressed mscFv1C9 arrested cell cycles via inhibiting the FGF‐1 intracrine pathway 12, 13. However, FGF‐1 works in both intracrine and paracrine pathways.…”
Section: Resultsmentioning
confidence: 99%
“…Next, we tested the effects of hscFv1C9 in cancer cells. As we had previously tested mscFv1C9 in breast cancer cells, 12,13 MDA-MB-231 was firstly used in cell proliferation and cell cycle tests.…”
Section: Humanization Of Mscfv1c9mentioning
confidence: 99%